Easy Numerical Method to Solution a System of Linear Volterra Integral Equations - Kaleel, Ahlam J; Omran, Huda H; Majeed, Salam J (Al-Nahrain Journal of Science, 2011)
In this paper, we present an adapted method for solving systems of linear Volterra integral equations of the second kind. This method is based on the Simpson's rule. We used two numerical examples to show the accuracy and simple of our method by comparison with known methods.